Comparison of Public Mental Health in Nigeria During the Pandemic and the New Normal - Aduwera Akerele Snema (PSPP JOURNALS, 2022)
Public mental health in Nigeria during the COVID-19 pandemic and the “new normal” that followed after the pandemic. We will analyze the impact of the pandemic on the mental health of the Nigerian people and how society has responded. In addition, we will also evaluate policies that have been implemented by the government and health institutions to address mental health problems caused by the pandemic. The COVID-19 pandemic has caused widespread anxiety and depression around the world, including in Nigeria. Some of the factors causing mental health problems in Nigeria during the pandemic include social isolation, economic uncertainty and fear of infection. However, after the pandemic, there have been some changes in Nigerian society that have made the mental health situation better compared to the pandemic, such as better access to mental health services, and stronger social support. Meanwhile, the Nigerian government has issued policies aimed at addressing mental health problems resulting from the pandemic, such as free counseling services and mental health support programs. However, there are still several obstacles that impede the effectiveness of this policy, such as a lack of adequate medical personnel, lack of access to mental health services in rural areas, and lack of financial support from the government. Overall, the COVID-19 pandemic has negatively affected the mental health of the Nigerian people. However, with the positive changes in society and the policies implemented by the government, it is hoped that the current mental health situation in Nigeria will be better than during the pandemic. However, there is still a need for stronger efforts from the government and health institutions to tackle mental health problems in Nigeria.